Equity in English Language Education in West Sulawesi: Challenges and Opportunities through the Lens of Capability Approach - Imansari, Nurul; Mega Januarti Putri, Andi (Universitas Muhammadiyah Jember, 2024)
This study explores the English language learning experiences of high school students in a rural school in West Sulawesi, Indonesia, through the Capability Approach. English proficiency is vital for national development, yet students in remote areas face numerous barriers that hinder their ability to learn the language, exacerbating social inequalities. This research fills a gap in understanding how these challenges affect students' educational outcomes in underprivileged regions. Through interviews and field observations, the study reveals the significant influence of socio-economic and environmental factors on students' abilities to engage with and benefit from English instruction in rural West Sulawesi. The findings indicate that students with limited resources are disproportionately affected, significantly constraining their ability to develop essential language skills. Furthermore, the study underscores the urgent need for targeted interventions, such as improved teaching quality and increased support for rural students, to address these inequalities. By promoting educational equity and bridging the gap between urban and rural English language education, these interventions can create more equal opportunities for students, fostering broader national development.